The Impact of Corporate Governance on Dividend Pay-out Ratio Policy During the Covid-19 Era: The study case in the Basic Material Industry in Indonesia - Hartono, Wendra; Laturette, Kazia; Gunawan, Kartikasari (AIBPM Publisher, 2023)
The purpose of this study is to analyze the impacts of Good Corporate Governance during the Covid -19 era on the dividend payout rasio policy in Indonesia. During Covid-19 era, the Basic Materials industry has faced big challenges due to lock down policy occured in many big areas which can lead to disruptive global economic supply chain. Due to lock down, the number of demands for basic materials has increased, meanwhile the price is becoming more expensive, because there was scarcity to get basic materials in the market. Increasing income in many Basic Material industry, can cause the percentage payment of dividends during the year of 2020 proposed by Board of Directors and Board of Commissioners. In this research will show and compare the condition of Basic Material industry before and during Covid-19 pandemic. This reseach is categorized as a quantitative reseach which the sample used is gathered from secondary data, financial report, from basic material industry for public listed company on the Indonesia Stock Exchange during 2018 – 2020, a total of 43 companies. There are 4 independent variables which is used in this study, which are the Independent Commissioner, the Board of Directors, the Board of Commissioners and the Audit Committee, meanwhile the dependent variable is dividend payout ratio.